Ancient China - Simpson, Judith ([Alexandria, Va.] : Time-Life Books, 1996)
An informative account of the more than 7,000-year-old civilization of China including insights into the individuals who helped shape this country.
Includes index.
School Library Journal
Library Talk
5.5
3-6
Keywords: China -- Civilization -- Juvenile literature; China -- Civilization; China -- Civilization